Pengaruh Pengungkapan CSR, Enterprise Risk Management, Profitabilitas, dan Good Corporate Governance terhadap Nilai Perusahaan - Yunita Setyo Pawestri; Enny Susilowati Mardjono; Anna Sumaryati; Purwantoro Purwantoro (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The purpose of this study is to examine the relationship between CSR, ERM, and profitability on firm value, as well as to analyze the role of the independent board of commissioners as a proxy for GCG in moderating that relationship. The method used in this study is a quantitative approach using secondary data obtained from the annual reports and sustainability reports of companies in the non-cyclical consumer sector listed on the Indonesia Stock Exchange. The research sample consisted of 22 companies with an observation period from 2022 to 2024. Purposive sampling was used to determine the research sample. Data analysis was conducted using multiple linear regression and Moderated Regression Analysis (MRA), processed using SPSS version 26. The results reveal that CSR and ERM do not have a significant effect on firm value. Conversely, profitability, as proxied by ROE, has a positive and significant effect on firm value. Furthermore, the independent board of commissioners, as a proxy for GCG, is unable to moderate the effects of CSR or ERM on firm value but is shown to strengthen the effect of profitability on firm value. This study focuses exclusively on companies in the non-cyclical consumer sector. Therefore, future researchers are advised to examine different sectors and consider additional factors that may influence the value of these companies in order to obtain a wider range of results